Behavioral Determinants of Business Continuity in Public Drinking Water Utilities (PDAM) in East Nusa Tenggara of Indonesia - Gana, Frans; Lay, Elly; Dthan, Fred M.; Handayani, Struce; Bessie, Juita L. D. (Jurnal Manajemen Pelayanan Publik, 2024)
The research pointed out the escalating challenges faced by the Indonesian Public Drinking Water Utilities (PDAMs) in ensuring water access, emphasizing the need for sustainable practices. The primary research problems are deliberately around understanding how CSR practices, corporate culture, and leadership styles impact business continuity in the context of water management utilities. The objective is to explore the relationships between CSR, corporate culture, leadership styles, and business continuity in PDAMs. The data were collected through structured self-administered questionnaires distributed to 100 employees of PDAM in East Nusa Tenggara of Indonesia, assessing their perceptions of CSR practices, corporate culture, leadership styles, and business continuity. The Likert-type scale responses were analyzed, revealing significant associations between these variables. Findings indicate that CSR initiatives positively contribute to business continuity, aligning with the leader's vision of community impact. The unique corporate culture, rooted in strong spiritual values, fosters a distinct work atmosphere and influences community habits. Additionally, a distinctive leadership style, treating employees as family, positively impacts employee attitude and business sustainability. While providing valuable insights, the study acknowledges limitations in generalizability and recommends further research for a comprehensive understanding of these dynamics.